Diversifying Quranic revision methods using gamification-based teaching material for tahfiz education - Abd Muhaimin Ahmad; Azman Ab Rahman; Muhammad Hafiz Saleh; Zainora Daud (Institute of Advanced Engineering and Science, 2024)
This study discusses the development procedure of the global tahfiz game (GTG) as a teaching aid for the Quranic revision subject for tahfiz students based on the gamification concept. Comprehensive design and development research (DDR) was used as the research method. The analysis includes conceptual and material development, expert evaluation, testing, and the final product. The development of concepts and materials used in this gamification was based on the theoretical framework of mechanics, dynamics, and aesthetics (MDA), with the application of tahfiz education elements. To examine the ability of GTG prototype to tackle the users’ needs, we have conducted the usability analysis. The expert teacher's mean score for the trial run on this gamification was high at 4.85. The trial run score for student participants was also high (4.45). The result demonstrated that most of the constructs are perceived at a high level by respondents. Thus, this indicated the high usability of GTG to be used as a teaching aid for a Quranic revision subject. The gamification of Quranic tahfiz based on board games has been finalized through recommendations and improvements based on the evaluation. The study findings are expected to be useful for educational institutions or researchers in developing teaching materials using the MDA framework for gamification, particularly in the field of Islamic education.